Auroral Observations at Syowa Station, 1970-1971 (Reports of the Japanese Antarctic Research Expedition) - Hiroshi FUKUNISHI (Antarctic Record, 1972)
The auroral observations carried out by the 11th wintering party of the Japanese Antarctic Research Expedition, 1970-1971, are ; 1. Photographic, observations of auroras with 16mm and 35mm all-sky cameras on routine basis. 2. Visual and photographic observations of auroras. 3. Observations of the space and time variations of proton auroras with the H_β tilting-filter meridian-scanning photometer and electron auroras with the multicolor meridian-scanning photometers. 4. Observations of auroral pulsations with the zenith photometers. The principal aim of these observations is to study the dynamical morphology of proton and electron auroras during magnetospheric substorms. A high time-resolution scanning photometer was constructed to measure the H_β emissions in proton auroras. The equipment consists of the coelostat for scanning the sky along the geomagnetic meridian and the tilting-filter photometer for detecting the intensity and Doppler shift of the H_β emission. The scanning period of the coelostat was 45s, and the tilting period of the filter was 1s. The lower threshold of the detection was 0.25R/Å. In order to study the space and time variations of the electron flux and energy spectra of auroral electrons, observations with the multicolor meridian-scanning photometers were carried out. The scanning period of these photometers was 5s. The observed emission lines were N_2^+_λ4278, OI_λ5577 and OI_λ6300. The minimum detectable intensities of the photometers were 100R, 100R and 30R, respectively for these emissions. The photographic observations were carried out with an improved model of 35mm all-sky camera mounted with a fish-eye lens.